The Need for Pediatric Palliative Care in Romania: A Retrospective Study (2022–2023) Based on Quantitative Research and Analysis of Secondary Statistical Data - Mihaela Hizanu Dumitrache; Mădălina Duceac Covrig; Dana Elena Mîndru; Alina Plesea Condratovici; Geta Mitrea; Eva Maria Elkan; Antoanela Curici; Bogdan Gafton; Letiția Doina Duceac (Medicina)
Background and Objectives: Estimating the need for palliative care for children is a crucial step in addressing the needs of children facing life-threatening conditions, while providing a powerful argument to combat unacceptably wide disparities in access to care. The need for palliative care for children in Romania remains insufficiently quantified. More accurate estimates are indispensable to assess the true extent of need and to support adequate policy responses. Materials and Methods: This retrospective cross-sectional study aimed to estimate the need for pediatric palliative care in Romania for 2022–2023. We analyzed secondary data obtained from the General Directorates of Social Assistance and Child Protection (DGASPC) in 41 counties and the six sectors of Bucharest. The analysis focused on life-limiting conditions as defined by the WHO Annex 3, Order no. 253/2018. Results: The study identified 14,499 pediatric cases with palliative care needs, showing a highly uneven national distribution, especially across diagnostic groups and age categories. We observed a higher number of cases in rural areas (7553) compared with urban areas (6946). Our own data do not include resource estimates; however, prior reports indicate only 50 palliative care beds for children in Romania. Conclusions: This study reveals a substantial and unevenly distributed need for pediatric palliative care in Romania, with notable disparities across age groups, diagnostic categories, and urban-rural areas. The identification of 14,499 eligible cases underscores the urgency of developing targeted policies and allocating adequate resources to ensure equitable access to specialized palliative services for all children in need.